2015
DOI: 10.1017/s1355617715000235
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Psychological Symptoms are Associated with Reduced Inhibitory Control, not General Executive Dysfunction

Abstract: Although there is mounting evidence that greater PTSD symptoms are associated with reduced executive functioning, it is not fully understood whether this association is more global or specific to certain executive function subdomains, such as inhibitory control. We investigated the generality of the association between PTSD symptoms and executive function by administering a broad battery of sensitive executive functioning tasks to a cohort of returning Operation Enduring Freedom/Operation Iraqi Freedom Veteran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
85
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 58 publications
9
85
0
4
Order By: Relevance
“…Previous studies in Iraq and Afghanistan Veterans with PTSD revealed impaired performance on tasks that require the inhibition of inappropriate motor responses (Swick et al, 2012; DeGutis et al, 2015). This replicable response inhibition deficit has been seen in other PTSD populations (Vasterling et al, 1998; Falconer et al, 2008a; Wu et al, 2010) and stands in contrast to the present results.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies in Iraq and Afghanistan Veterans with PTSD revealed impaired performance on tasks that require the inhibition of inappropriate motor responses (Swick et al, 2012; DeGutis et al, 2015). This replicable response inhibition deficit has been seen in other PTSD populations (Vasterling et al, 1998; Falconer et al, 2008a; Wu et al, 2010) and stands in contrast to the present results.…”
Section: Discussionmentioning
confidence: 97%
“…To separate the contribution of strategic changes and ability factors, we have also successfully utilized signal detection analyses of gradCPT (Esterman, Reagan, Liu, Turner, & DeGutis, 2014). Finally, several recent studies suggest that the gradCPT is ecologically valid in that a variant of the gradCPT correlates with real-world attentional problems (Rosenberg, et al, 2013) and performance on the original version is impaired in patient populations with traditionally poor sustained attention (Auerbach, et al, 2014; DeGutis, et al, in press). Together, this suggests the gradCPT is a powerful tool to capture changes in sustained attention ability throughout the lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, this measure was chosen as a covariate to determine if broad cognitive skills explain hypothesized associations. This is important given that anxiety symptoms associated with post-traumatic stress have been found to be specific to inhibition as opposed to general executive dysfunction (DeGutis et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Inhibition is the ability to refrain from responding or attending to tempting/distracting information, objects, thoughts, or activities. Indeed, those who have low inhibition are more likely to attend to anxious thoughts, and have greater difficulty shifting their attention away from such thoughts, than those with high inhibition (DeGutis et al, 2015; Joormann & Gotlib, 2010; Schmeichel & Tang, 2015). Others have argued that better inhibition is associated with less anxiety via the ability to flexibly and adaptively respond to oneā€™s environment using optimal coping strategies (e.g., Martel, Nokolas, & Nigg, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation